Human SP-D Acts as an Innate Immune Surveillance Molecule Against Androgen-Responsive and Androgen-Resistant Prostate Cancer Cells - Thakur, Gargi; Prakash, Gagan; Murthy, Vedang; Sable, Nilesh; Menon, Santosh; Alrokayan, Salman H.; Khan, Haseeb A.; Murugaiah, Valarmathy; Bakshi, Ganesh; Kishore, Uday; Madan, Taruna (Frontiers in Oncology, 2019)
Surfactant Protein D (SP-D), a pattern recognition innate immune molecule, has been implicated in the immune surveillance against cancer. Recently, an association between decreased SP-D expression in human prostate adenocarcinoma and an increased Gleason score and severity has been reported. In the present study, we evaluated the SP-D expression in primary prostate epithelial cells (PrEC) and prostate cancer cell lines. LNCaP, an androgen dependent prostate cancer cell line, exhibited significantly lower mRNA and protein levels of SP-D than PrEC and the androgen-independent cell lines (PC3 and DU145). A recombinant fragment of human SP-D (rfhSP-D), composed of trimeric neck and carbohydrate recognition domains, showed a dose- and time- dependent binding to prostate cancer cells via its CRD region. rfhSP-D induced significantly apoptosis in tumour explants and primary tumor cells isolated from tissue biopsies of metastatic prostate cancer patients. While the viability of PrEC was not altered by rfhSP-D, the rfhSP-D LNCaP (p53+/+) and PC3 (p53-/-) cells showed reduced cell viability in a dose- and time- dependent manner, as they were arrested in G2/M and G1/G0 phase of the cell cycle, respectively. The rfhSP-D treated LNCaP cells showed a significant upregulation of p53 whereas a significant downregulation of pAkt was observed in both PC3 and LNCaP cell lines. The rfhSP-D-induced apoptosis signalling cascade involved upregulation of Bax:Bcl2 ratio, cytochrome c and cleaved products of caspase 7. Thus, rfhSP-D induced apoptosis in prostate tumor explants as well as in androgen-responsive and androgen-resistant prostate cancer cells via p53 and pAkt pathways. Thus, by exploiting multiple apoptotic pathways, rfhSP-D treatment can overcome tumorigenesis of varied forms of prostate cancer.